OP0331 A novel humanized effector-deficient fcyriia antibody inhibits immune complex mediated proinflammatory responses. (15th June 2017) - Chen, B; Vousden, K; Turman, S; Sun, H; Wang, S; Vinall, L; Kemp, B; Kasturiangan, S; Grant, E; Hinrichs, MJ; Eck, S; DiGiandomenico, A; et al.
Abstract : Background: Collectively, the cell surface Fc region of IgG receptors (FcγRs) engage soluble IgG and IgG containing immune complexes and trigger activation or inhibtory signals that play a critical role in the regulation of immune responses. The low affinity FcγRIIA (CD32A) is the most widely expressed activating FcγR in humans and appears to drive autoantibody and immune complex mediated autoimmune disorders. So far a therapeutic targeting this receptor has not been developed. Objectives: To generate and characterize a novel humanized effector-deficient FcγRIIA antibody (MEDI9600) for clinical development. Methods: The mode of action of MEDI9600 was assessed by confocal microscopy, whole blood internalization, and binding competition assays. Multiple cell based assays were used to measure autoantibody and immune complex mediated responses. The safety of MEDI9600 was assessed in in vitro by neutrophil migration, activation and opsonophagocytic killing assays. Safety and pharmacokinetics were examined in vivo in a single-dose PK/PD study in cynomolgus monkey. Results: We generated a humanized effector-deficient FcγRIIA antibody (MEDI9600) that potently blocks both autoantibody and immuno complex-mediated proinflammatory responses from a variety of cell types. This includes the inhibition of Toll-like receptor stimulatory immune complexes that induce type I Interferons from pDC, and the inhibition of anti-neutrophil cytoplasmic antibody (ANCA) induced production of reactive oxygen species from neutrophils, which are associated with the pathogenesis of systemic lupus and ANCA vasculitis respectively. MEDI9600 specifically binds FcγRIIA and its suppressive activity is attributed to its capacity to block ligand engagement and to internalize the receptor from the cell surface. Moreover, in vivo studies indicate that MEDI9600 has a favorable pharmacokinetic and safety profile. Conclusions: We have generated MEDI9600, a specific humanized antibody antagonist of FcγRIIA with null effector function that may provide a novel therapeutic approach in the treatment of immune complex mediated diseases. Disclosure of Interest: None declared